A5_11 Saving Alderaan 2: Momentum Strikes Back - Newland, Rhys; Graham, Thomas; Kaiser, Felix; Keaney, Connor; Pankhania, Kishen (Physics Special Topics, 2022)
This paper will look into whether the mass of silver required to successfully reflect and absorb the Death Star's (DS's) laser intent on destroying Alderaan, in the PST paper Saving Alderaan: A Star Wars Story, could be accelerated by the DS's laser out of stable orbit and into Alderaan with enough kinetic energy to overcome the previously calculated gravitational binding energy of Alderaan, thus destroying it.